Mothers intention and preference to use mobile phone text message reminders for child vaccination in Northwest Ethiopia. Issue 1 (19th February 2021) - Mekonnen, Zeleke Abebaw; Gelaye, Kassahun Alemu; Were, Martin C.; Tilahun, Binyam
Abstract : Objectives: With the unprecedented penetration of mobile devices in the developing world, mHealth applications are being leveraged for different health domains. Among the different factors that affect the use of mHealth interventions is the intention and preference of end-users to use the system. This study aimed to assess mother's intention and preference to use text message reminders for vaccination in Ethiopia. Methods: A cross-sectional study was conducted among 460 mothers selected through a systematic random sampling technique. Initially, descriptive statistics were computed. Binary logistic regression analysis was also used to assess factors associated with the outcome variable. Results: In this study, of the 456 mothers included for analysis, 360 (78.9%) of mothers have intention to use text message reminders for vaccination. Of these, 270 (75%) wanted to receive the reminders a day before the vaccination due date. Mothers aged 35 years or more (AOR=0.35; 95% CI: 0.15 to 0.83), secondary education and above (AOR=4.43; 95% CI: 2.05 to 9.58), duration of mobile phone use (AOR=3.63; 95% CI: 1.66 to 7.94), perceived usefulness (AOR=6.37; 95% CI: 3.13 to 12.98) and perceived ease of use (AOR=3.85; 95% CI: 2.06 to 7.18) were predictors of intention to use text messages for vaccination. Conclusion: In conclusion, majority of mothers have the intention to use text message reminders for child vaccination. Mother's age, education, duration of mobile phone use, perceived usefulness and perceived ease of use were associated with intention of mothers to use text messages for vaccination. Considering these predictors and user's preferences before developing and testing text message reminder systems is recommended.